2022
DOI: 10.1002/er.8212
|View full text |Cite
|
Sign up to set email alerts
|

Self‐standing 2D tin‐sulfide‐based heterostructured nanosheets: An efficient overall urea oxidation catalyst

Abstract: Summary In this work, SnS/SnS2 heterostructured film on a nickel foam (NF) through solution process was grown and employed directly as cathode and anode to the urea oxidation reaction (UOR). The as‐fabricated SnS/SnS2 film achieves high efficiency toward UOR with a lower potential of 1.38 V vs RHE to deliver 50 mA cm−2, which is approximately 200 mV less than the potential demanded for the oxygen evolution reaction (OER). More importantly, the electrolyzer consisting of two identical electrodes with the SnS/Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…[11][12][13][14][15] Consequently, recently extensive attention has been paid to the UOR as a promising alternative anodic reaction for energy-efficient hydrogen production in water electrolysis. [16][17][18][19][20][21][22][23][24][25][26] In addition, the urea-rich wastewater from the fertilizer industry, agricultural residues, and human/animal wastes are abundantly available and easily transportable resources of hydrogen. Therefore, the UOR as an alternative anodic reaction to the OER can reduce the cost of hydrogen production and decontaminate urea waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] Consequently, recently extensive attention has been paid to the UOR as a promising alternative anodic reaction for energy-efficient hydrogen production in water electrolysis. [16][17][18][19][20][21][22][23][24][25][26] In addition, the urea-rich wastewater from the fertilizer industry, agricultural residues, and human/animal wastes are abundantly available and easily transportable resources of hydrogen. Therefore, the UOR as an alternative anodic reaction to the OER can reduce the cost of hydrogen production and decontaminate urea waste.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37][38][39][40] However, it is worth noting that regardless of the potential bias, the maximum UOR current density, which reects the urea oxidation rate, is oen reported to be less than 500 mA cm −2 . [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][32][33][34][35][36][37][38][39][40] This is because of the detrimental competition existing between the UOR and OER, resulting in a current tradeoff region in the anodic polarization curves. 17,[41][42][43][44][45] Although many works have been reported on the catalytic performance of various catalysts for easily oxidizable organic molecules including urea, hardly any work can be found in the literature regarding the fundamental understanding of the catalytic activity limitation and reaction selectivity during urea electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that transition metal-based compounds such as oxides, [22][23][24][25][26][27][28][29] chalcogenides, [30][31][32][33] nitrides, [34][35][36] and phosphides [37][38][39] are promising alternatives to RuO 2 -, IrO 2 -and Pt-based electrocatalysts. In order to further lower the energy barrier of the anodic reaction for efficient hydrogen production in water electrolysis, various proxy anodic reactions of easily oxidizable molecules such as hydrazine, 40,41 sulfion, 42,43 urea, [43][44][45][46][47][48] alcohols, [49][50][51] and glucose [52][53][54] having lower thermodynamic potentials have been explored. Among them, the electrochemical oxidation of glucose (GOR: glucose oxidation reaction) is economically promising because it can feasibly be derived from the abun-dantly available biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Heterojunctions have also been constructed for photocatalytic hydrogen evolution, photocatalytic nitrogen xation, electrocatalytic hydrogen evolution, urea oxidation reaction, and the ORR. [25][26][27][28] Nevertheless, heterojunction design is rarely reported for the bifunctional 2e − ORR and EOP.…”
Section: Introductionmentioning
confidence: 99%